Context in Generalized Conversational Implicatures: The Case of Some - Dupuy, Ludivine E.; Van der Henst, Jean-Baptiste; Cheylus, Anne; Reboul, Anne C. (Frontiers in Psychology, 2016)
There is now general agreement about the optionality of scalar implicatures: the pragmatic interpretation will be accessed depending on the context relative to which the utterance is interpreted. The question, then, is what makes a context upper- (vs. lower-) bounding. Neo-Gricean accounts should predict that contexts including factual information should enhance the rate of pragmatic interpretations. Post-Gricean accounts should predict that contexts including psychological attributions should enhance the rate of pragmatic interpretations. We tested two factors using the quantifier scale <all, some>: (1) the existence of factual information that facilitates the computation of pragmatic interpretations in the context (here, the cardinality of the domain of quantification) and (2) the fact that the context makes the difference between the semantic and the pragmatic interpretations of the target sentence relevant, involving psychological attributions to the speaker (here a question using all). We did three experiments, all of which suggest that while cardinality information may be necessary to the computation of the pragmatic interpretation, it plays a minor role in triggering it; highlighting the contrast between the pragmatic and the semantic interpretations, while it is not necessary to the computation of the pragmatic interpretation, strongly mandates a pragmatic interpretation. These results favor Sperber and Wilson’s (1995) post-Gricean account over Chierchia’s (2013) neo-Gricean account. Overall, this suggests that highlighting the relevance of the pragmatic vs. semantic interpretations of the target sentence makes a context upper-bounding. Additionally, the results give a small advantage to the post-Gricean account.